Lidar observations of natural and volcanic-ash-induced cirrus clouds - Rolf, Christian (Forschungszentrum Jülich GmbH Zentralbibliothek, Verlag, 2013)
Cirrus clouds - which consist solely of ice particles - influence the Earth’s radiation budget and thus the climate system since they scatter the incoming solar radiation (cooling effect) and absorb the outgoing radiation of the Earth (warming effect). However, this influence has not yet been quantified. The purpose of this thesis is to extend our knowledge about cirrus with the help of lidar measurements in combination with model simulations. In the first part, observations of cirrus clouds made with a backscatter lidar over Jülich are presented, focusing on obtaining a representative cirrus climatology. The cirrus clouds are evaluated with a temporal average extinction profile by considering a multiple scattering correction. By using additional meteorological data, the climatological observations are analyzed under macrophysical, radiative, and microphysical aspects and considered to be representative in comparison to other mid-latitude lidar climatologies. Most of the observed cirrus clouds were generated due to synoptic weather patterns (e.g. frontal systems), showing a large vertical thickness of about 2.2 km and occurring mostly directly below the tropopause. Mean and median values of optical depth are found to be around 0.28 and 0.12 (range: 0.002 - 3), respectively. The most frequently observed ice water content (IWC) was found to be 6 ppmv (range: 0.01 - 400 ppmv). The lowest detected IWC values from aircraft in situ measurements (∼ 0.01 ppmv) are confirmed by the lidar observations. This result is of importance, since up to now it has been unclear whether in situ aircraft instruments were able to detect the thinnest cirrus clouds. In the second part of the thesis, heterogeneous ice formation induced by volcanic ash from the Eyjafjallajökull volcano eruption in April 2010 is investigated based on a lidar observation of an ash-induced cirrus cloud in combination with model simulations along air mass trajectories. The microphysical properties of the cirrus cloud can only be represented by the ...